2014
DOI: 10.1121/1.4869089
|View full text |Cite
|
Sign up to set email alerts
|

A three dimensional investigation into the acoustic performance of dissipative splitter silencers

Abstract: Splitter silencers are found in ventilation and gas turbine systems and consist of parallel baffles of porous material placed within a duct so that they split the mean gas flow. Theoretical investigations into dissipative splitter silencers have generally been limited to two dimensions and this limits the analysis to finding the silencer eigenmodes or, for a finite length silencer, to rectangular baffles only. In this article a numerical point collocation approach is used to extend theoretical predictions to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…This is important in delivering fast and effective commercial design facilities for applications where mean flow velocities may be significant, such as gas turbine exhaust systems. It also delivers a method viable for studying the effects of flow on more complex silencer designs that require a three dimensional approach, see for example the designs studied by Kirby et al [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important in delivering fast and effective commercial design facilities for applications where mean flow velocities may be significant, such as gas turbine exhaust systems. It also delivers a method viable for studying the effects of flow on more complex silencer designs that require a three dimensional approach, see for example the designs studied by Kirby et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the purpose of this article is to present and validate a theoretical methodology for use in bespoke design applications and here it is shown that one may use the point collocation method to do this. This simplified approach has significant advantages for larger and more complex silencers such as the three dimensional silencers studied by Kirby et al [32].…”
Section: Lowering Computational Demandsmentioning
confidence: 99%
“…The characteristic impedances of the two guides, z i /h i (see Equations. (19,20), are found to be either infinite ou zero. It is interesting to interpret these results.…”
Section: Lossless Lattices; Cut-off Frequenciesmentioning
confidence: 97%
“…Related problems are tubes with branched resonators, which can be uncoupled [10,11] or coupled [12], or with honeycomb cavities [13,14]. Other kind of systems are splitter silencers with perforated facing [15][16][17][18][19][20]. This generic problem is that of a periodic lattice of two waveguides coupled by perforations.…”
Section: Introductionmentioning
confidence: 99%
“…This type of silencer has also been analysed using a boundary element approach, see for example Zhou et al [9] and Wang and Wu [10]. It is common also to use the more complex bar type silencer for larger applications, and these were analysed by Kirby et al [11], and recently by Yang et al [12]. The analysis of silencer performance reported in these articles clearly demonstrate that dissipative silencers can be very effective over the medium to high frequency range; however, even the more complex designs find it difficult to deliver acceptable levels of attenuation at low frequency.…”
Section: Introductionmentioning
confidence: 99%